Effects of Initial Eye Position on Saccades Evoked by Microstimulation in the Primate Superior Colliculus: Implications for Models of the SC Read-Out Process - Groh, Jennifer M. (Frontiers in Integrative Neuroscience, 2011)
The motor layers of the superior colliculus (SC) are thought to specify saccade amplitude and direction, independent of initial eye position. However, recent evidence suggests that eye position can modulate the level of activity of SC motor neurons. In this study, we tested whether initial eye position has an effect on microstimulation-evoked saccade amplitude. High (>300 Hz) and low (<300 Hz) frequency microstimulation was applied to 30 sites in the rostral part of the SC of two monkeys while they fixated one of six different locations. We found that the amplitude of the evoked saccades decreased with more contralateral initial eye positions. This effect was more pronounced in low frequency- compared to high frequency-evoked saccades, although it was present for both. Replication of these findings in head-free experiments showed that the effect of initial eye position was not due to physical constraints imposed by the oculomotor range. In addition to the effect of eye position on saccade amplitude, we also observed an increase in saccade latency and a decrease in the probability that microstimulation would evoke a saccade for low frequency stimulation at more contralateral eye positions. These findings suggest that an eye position signal can contribute to the read-out of the SC. Models of the saccadic pulse-step generator may need revision to incorporate an eye-position modulation at the input stage.